Self-Censorship and Censorship in Nitobe Inazo, Bushido: The Soul of Japan, and Four Translations of the Work - Rodríguez Navarro, María; Beeby, Allison (TTR)

(untitled) (Association canadienne de traductologie, 2010)
This paper looks at self-censorship and censorship in Bushido: The Soul of Japan (1900) by Nitobe, Inazo (1862-1933) as well as in four different translations of the book. In Bushido, probably the best known of Nitobe’s books, the renowned Japanese writer and diplomat tried to act as an inter-cultural mediator between East and West and export the concepts and values of Bushido (the path of the samurai). Nitobe was descended from one of the great samurai families, but he converted to Christianity, married an American Quaker from Philadelphia and studied widely in the US and in Europe. Bushido was a valiant attempt to “translate” the ethical code of the samurais for the West, but perhaps in so doing Nitobe idealized the samurai caste by domesticating their values and teaching in order to bring them closer to Christian values and teaching. The main purpose of his book was to make Japanese culture acceptable to and valued by the West and in particular Philadelphia at the beginning of the 20th century, but he also had to assure the approval of the imperial authorities.The original text was written in English, which was not Nitobe’s mother tongue, and it can be studied as a self-translation that involves self-censorship. Writing in a foreign language obliges one to “filter” one’s own emotions and modes of expression. To a certain extent, it also limits one’s capacity for self-expression. Alternatively, it allows the writer to express more empathy for the “other culture.” Furthermore, one is much more conscious of what one wants to say, or what one wishes to avoid saying, in order to make the work more acceptable for intended readers.The four translations are the Spanish translation by Gonzalo Jiménez de la Espada (1909), the French translation by Charles Jacob (1927), the Japanese translation by Yanaihara Tadao (1938) and the Spanish translation by General José Millán-Astray (1941). A descriptive, diachronic study of the translation of selected cultural references shows the four translations to be good examples of the way translations vary over time. They also illustrate the relationship between context, pretext and text (Widowson, 2004) and the visibility or invisibility of the translator (Venuti, 1995). We have also found it useful to draw on skopos theory, as well as some aspects of the Manipulation School, in particular ideology, censorship and the emphasis on translation between distant languages and cultures.The analysis of the four translations shows that censorship of cultural references is evident during periods of conflict (such as the Japanese translation of 1938 and the Spanish translation of 1941). We hope to show that the context/pretext of the translator led to such manipulative or censorial translation decisions that Nitobe’s skopos was lost in at least one of the translations.